1989
DOI: 10.1104/pp.91.2.702
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally Regulated Expression of the Gene Family for Cytosolic Glutamine Synthetase in Pisum sativum

Abstract: In Pisum sativum, two classes of genes encode distinct isoforms of cytosolic glutamine synthetase (GS). The first class comprises two nearly identical or "twin" GS genes (GS341 and GS132), while the second comprises a single GS gene (GS299) distinct in both coding and noncoding regions from the "twin" GS genes. Gene-specific analyses were used to monitor the individual contribution of each gene for cytosolic GS during root nodule development and in cotyledons during germination, two contexts where large amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
2
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 26 publications
2
45
2
1
Order By: Relevance
“…The high-level expression of the gene for cytosolic GS3A in the vasculature is particularly intense in the cotyledons of germinating seedlings, where glutamine serves as the transport form of nitrogen from seed storage reserves to the developing plant. These findings in transgenic tobacco correlate well with the abundant accumulation of GS3A mRNA in germinating pea cotyledons and in nitrogen-fixing root nodules (12,18). Since expression of the pea GS3A gene in tobacco cotyledons is confined to the vasculature, it will be of interest to determine whether induced chlorophyll a/b binding protein).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The high-level expression of the gene for cytosolic GS3A in the vasculature is particularly intense in the cotyledons of germinating seedlings, where glutamine serves as the transport form of nitrogen from seed storage reserves to the developing plant. These findings in transgenic tobacco correlate well with the abundant accumulation of GS3A mRNA in germinating pea cotyledons and in nitrogen-fixing root nodules (12,18). Since expression of the pea GS3A gene in tobacco cotyledons is confined to the vasculature, it will be of interest to determine whether induced chlorophyll a/b binding protein).…”
Section: Discussionsupporting
confidence: 55%
“…"Sparkle" (Rogers Brothers Seed, Twin Falls, ID) constructed in "Lambda Dash" (Stratagene). Complete sequence analysis of each genomic clone (unpublished data) revealed that the genomic clone for chloroplast GS2 (GS2ct) corresponds to the GS185 cDNA (13), whereas the genomic clone for cytosolic GS (GS3ACY) corresponds to the GS341 cDNA (12,18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ineffective root nodules have been used to evaluate the role of NH4+ availability in nodule gene expression (1,2,12,37). In most studies, ineffective nodules were induced by mutant strains of rhizobia.…”
mentioning
confidence: 99%